The Role of Entrepreneurial Characteristics and Islamic Financial Behaviour in Improving Business Performance Toward the Welfare of Mustahik - Sheikha Naura; Muhammad Haris Riyaldi; Eka Nurlina; Najla Najla; Teuku Muhammad Syahrizal (International Journal of Kita Kreatif, 2026)
This study aims to analyze the role of business performance as a mediating variable in the relationship between entrepreneurial characteristics and Islamic financial behavior on the welfare of Mustahik (Zakat recipients). The research was conducted through the BAZNAS Microfinance Village (BMV) Program in Banda Aceh using a quantitative approach with both primary and secondary data. The population consisted of micro entrepreneurs in Banda Aceh, with a sample of 103 determined using the Slovin formula and selected through purposive sampling based on predefined criteria. Data were analyzed using path analysis to examine both direct and indirect effects among the variables. The results of the study indicate that entrepreneurial characteristics and sharia financial behavior have a positive and significant effect on business performance. Moreover, entrepreneurial characteristicsalso have a positive and significant influence on the welfare of Mustahik. However, sharia financial behavior and business performance do not show a significant effect on Mustahik welfare. Furthermore, business performance is proven to partial mediatethe relationship between entrepreneurial characteristics and Mustahik welfare.Conversely, business performance does not mediate the relationship betweensharia financial behavior and Mustahik welfare non-mediation.